Cytotoxicity and In Vitro Antileishmanial Activity of Antimony (V), Bismuth (V), and Tin (IV) Complexes of Lapachol - Marcele Neves Rocha; Paula Monalisa Nogueira; Cynthia Demicheli; Ludmila Gonçalvez de Oliveira; Meiriane Mariano da Silva; Frédéric Frézard; Maria Norma Melo; Rodrigo Pedro Soares (Bioinorganic Chemistry and Applications)
Leishmania amazonensis is the etiologic agent of the cutaneous and diffuse leishmaniasis often associated with drug resistance. Lapachol [2-hydroxy-3-(3′-methyl-2-butenyl)-1,4-naphthoquinone] displays a wide range of antimicrobial properties against many pathogens. In this study, using the classic microscopic in vitro model, we have analyzed the effects of a series of lapachol and chlorides complexes with antimony (V), bismuth (V), and tin (IV) against L. amazonensis. All seven compounds exhibited antileishmanial activity, but most of the antimony (V) and bismuth (V) complexes were toxic against human HepG2 cells and murine macrophages. The best IC50 values (0.17 ± 0.03 and 0.10 ± 0.11 μg/mL) were observed for Tin (IV) complexes (3) [(Lp)(Ph3Sn)] and (6) (Ph3SnCl2), respectively. Their selective indexes (SIs) were 70.65 and 120.35 for HepG2 cells, respectively. However, while analyzing murine macrophages, the SI decreased. Those compounds were moderately toxic for HepG2 cells and toxic for murine macrophages, still underlying the need of chemical modification in this class of compounds.